Variasi Warna Kaca pada Media Pengeringan terhadap Karakteristik Fisikokimia dan Mikrobiologi Permen Jeli Jahe (Zingiber officinale) - Muh. Doddy Pratama; M. Muhtar; M. Alif; Fahrizal Fahrizal (Pusat Penelitian dan Pengabdian Kepada Masyarakat, Politeknik Negeri Tanah Laut, 2021)
One step to producing ginger jelly candy is drying processing. Generally, this process is done by people using open drying method under the sunlight without considration of product quality eventhough it has lowcost production compare to conventional production that has been standarized. This research was to compare physical-chemical and microbiology characterization between variation of glass color in drying medium for ginger jelly candy (Zingiber officinale). Research methodology to analyze physical-chemical caharacterization consist of hedonic test (organoleptic), refractometre (Total Sugar), thermohygrometre (temperature and moisture) and gravymetre (moisture content), and microbiology characterization consist of total plate count for bacteria and fungi. Randomized complete design (oneway ANNOVA) result showed variation of glass color (P1 and P2) of drying medium was no effect on organoleptic result of ginjer jelly candy such as aroma (3.6 and 4.05), flavor (3.95 and 4.15), color (3.9 and 3.95) and texture (4.1 and 4.15) respectively, but it was effect to moisture content, total sugar and bacterial contamination numbers. Variation of glass color result from P1 was obtained higher compare to P2 on (21.43 % and 15.39 %) moisture content, (13.75 % and 11.75 %) total sugar and (22 cfu/g and 4.5 cfu/g) bacterial contamination numbers. Meanwhile, there was no growth of fungi contamination numbers on both treatments.